Rahasia Dzikir dengan Metode Tharikat Untuk Membentuk Pertahanan Mental dalam Mengatasi Gangguan Jiwa Rasa Takut (Fear) Akibat Stressor Wabah Covid-19 - Isep Zaenal Arifin (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2020)
AbstrakPsychology and Psychiatry must finally honestly admit that both are psychology which actually do not know about the true nature of the soul (nafs). What can be investigated and described by this science are only the various symptoms of the soul that can be observed. Therefore this discipline must be humble to look for other sources that can explain the true nature of the human soul. By knowing the true nature of the soul, all mental disorders and mental illnesses can be rooted and cured. This knowledge is none other than the Science of Tashawuf and tharikat. In this science there are various deep secrets of the human soul (lathifah, nafs, spirit) which cannot be uncovered by Western sciences including psychology and psychiatry. This paper will explain a little about the deepest dimension of human information found by the tharikat and is very useful to overcome mental disorders, especially fear (fear) due to the pandemic of the Covid-19 plague that increasingly undermined the soul of this nation through the technique of Dhikr tharikat so that spiritual power has spiritual energy enough to move the full potential of human life and build mental defenses